Application of Project-Based Worksheets on the Utilization of Rice Husk Charcoal Adsorbent to Reduce Groundwater Hardness in Develoving Students’ Scientific Performance - Khairunnisa, Hana Humaira; Sari , Sari; Sukmawardana , Yulia (IJCER (International Journal of Chemistry Education Research), 2025)
This study evaluates the effectiveness of project-based worksheets in developing students' scientific performance through practical application of rice husk charcoal adsorbents for groundwater hardness reduction. This is first study integrating project-based worksheets with practical application of rice husk charcoal for water hardness reduction for develoving students’ scientific performance in chemistry education. Using a pre-experimental one-shot case study design, 36 twelfth-grade students from SMKN 7 Bandung participated in a six-session practicum involving complexometric titration and adsorption processes. Students' scientific performance was assessed across five project stages using validated rubrics (0-100 scale). Rice husk charcoal adsorbents (0.2g and 0.5g) were tested against groundwater samples, with hardness measured through EDTA titration using established analytical protocols. Results demonstrated consistently high performance across all stages: problem identification (92.1%), project design (91.3%), implementation (89.8%), prototype development (89.8%), product evaluation (95.6%), and finalization (86.7%). Statistical analysis showed significant improvement in students' ability to connect theoretical concepts with practical applications, particularly in understanding complexometric titration mechanisms and adsorption principles. The adsorbent successfully reduced groundwater hardness below WHO standards (500 mg/L), validating both the environmental solution and pedagogical approach. This integrated methodology uniquely combines analytical chemistry education with sustainable environmental remediation, demonstrating measurable enhancement in students' scientific literacy, critical thinking, and problem-solving capabilities through authentic, hands-on learning experiences that address real-world water quality challenges.